Correlation Between Personal Hygiene And Hemoglobin Levels On Typhoid Fever Suspect Patients At Lirboyo General Hospital: Hubungan Personal Hygiene Dengan Kadar Hemoglobin Pada Penderita Suspek Demam Tifoid Di Rumah Sakit Umum Lirboyo - Farodis, Indana; Purnadianti, Mely (Universitas Muhammadiyah Sidoarjo, 2020)
Personal Hygiene is an effort made by individuals in maintaining personal hygiene to avoid disease. Personal Hygiene is closely related to typhoid fever, because its transmission can be through food and drinks which are contaminated with Salmonella typhi. WHO and UNICEF ​​on 2015 ranked Indonesia as the second worst sanitation country in the world after India. One of the laboratory tests which is used to observe anemia levels and polycythaemia is hemoglobin degree. The purpose of this study was to analyze the correlation between personal hygiene and hemoglobin levels on typhoid fever suspect patients at Lirboyo General Hospital. The research method used analytic survey with Cross Sectional Study approach and purposive sampling used as the sampling technique with 38 respondents. The results of the study mostly have worst personal hygiene quality of 31 people (81.6%) while respondents have good personal hygiene quality of 7 people (18.4%) and the of hemoglobin category on patients stated normal in 29 people (76.3%) while patients who have abnormal hemoglobin category in 9 people (23.7%). Based on statistical tests on personal hygiene by hemoglobin showed 0.876 p-value and > 0.05 sig value Conclusion which indicated no correlation between personal hygiene and hemoglobin on typhoid fever suspect at Lirboyo General Hospital.